A corrupção sistêmica do direito e a Operação Lava Jato: teoria dos sistemas de Niklas Luhmann aplicada - Almeida, Tiago de Lima (2025)
The present thesis will be dedicated to analyzing the Systems Theory and the Luhmannian concepts of structural coupling, operational closure, autopoiesis and allopoiesis seeking to make a theoretical approximation with Operation Car Wash, which meant an episode of systemic corruption in the Brazilian Legal System, due to the adoption of an alien code to the detriment of the Legal Code itself. When the elements of a different system enter and remain in it, without passing through the filter of the difference-code of the entering system, the phenomenon of allopoiesis occurs. The present research intends to demonstrate how Operation Car Wash meant the interference of the Political and Economic Systems over the Legal System, when, by force of illicit political pressure, judicial decisions were produced that were legally inconsistent and conflicting with the normative expectation that the Brazilian legal system offers to those under jurisdiction, without the law having its own mechanisms, conditions to react, which culminated in a disastrous political, economic and legal result for the country. Using Niklas Luhmann's Systems Theory as a theoretical framework, the research will address judicial independence and the Judiciary in Brazil, considering the function of constitutional courts in accordance with Systems Theory, especially the Federal Supreme Court. The research will also consider civil society, the media and social networks as co-responsible actors for the maintenance of democracy. It will also carry out the historicization of the Operation Car Wash, from the June Journay 2013, observing other relevant political facts until the arrest of President Luiz Inácio Lula da Silva and his removal from the electoral process, through a partial trial. At the end, it will point out the ways in which the forces around democracy have been reordered, after the necessary interference of the Supreme Court to revoke inconsistent legal decisions and put an end to the project of systemic corruption, precariously successful, whose consequences have actually operated in the legal system